THE EFFECT OF COMPENSATION ON JOB SATISFACTION WITH WORK MOTIVATION AS AN INTERVENING VARIABLE (Case Study at PT. Tiga Mutiara Nusantara Molding Section in Dolok Merawan District) - Eka Mayastika Sinaga; Christin Natalia Sianipar; Ranti Dwi Putri Saragih (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Based on the results of research and discussion regarding the effect of compensation on job satisfaction with work motivation as an intervening variable "at PT. Tiga Mutiara Nusantara Molding Section in Kec. Dolok Merawan, it can be concluded that: Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the compensation variable (X) influences the work motivation variable (Z). This reflects that the greater the compensation given by PT. Tiga Mutiara Nusantara will be more motivated by employees at work. Based on the results of the analysis of hypothesis 2 it can be concluded that it can be concluded that the second hypothesis is accepted, meaning that the Compensation variable (X) influences the Job Satisfaction variable (Y). This can be interpreted that the higher the compensation given, the more satisfied employees will be. Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is accepted, meaning that the variable Work Motivation (Z) affects the variable Job Satisfaction (Y). This reflects that if employees are motivated to eat, employees will be more satisfied at work. Based on the results of the analysis of hypothesis 4, it shows the direct influence of the Compensation variable (X) on the Job Satisfaction variable (Y). While the indirect effect is through the variable Work Motivation (Z). the indirect effect through the Work Motivation variable (Z) is smaller than the direct effect on the Job Satisfaction variable (Y).